RNA metabolism and gene expression in Archaea - Clouet-d'Orval, Béatrice (Springer, 2017)
This book focuses on the regulation of transcription and translation in Archaea and arising insights into the evolution of RNA processing pathways. From synthesis to degradation and the implications of gene expression, it presents the current state of knowledge on archaeal RNA biology in 13 chapters. Topics covered include the modification and maturation of RNAs, the function of small non-coding RNAs and the CRISPR-Cas defense system. While Archaea have long been considered exotic microbial extremophiles, they are now increasingly being recognized as important model microorganisms for the study of molecular mechanisms conserved across the three domains of life, and with regard to the relevance of similarities and differences to eukaryotes and bacteria. This unique book offers a valuable resource for all readers interested in the regulation of gene expression in Archaea and RNA metabolism in general.
Keywords: Archaebacteria -- Metabolism.; RNA -- Metabolism.; Molecular microbiology.; Nucleic acids.; Proteins.; Enzymology.; elektronické knihy; electronic books